The role of the agricultural sector in the legal system of national reductions of air pollution in the European Union under Directive 2016/2284 NEC - Goździewicz-Biechońska, Justyna (Przegląd Prawa Rolnego, 2019)
The aim of the article is to define the role of the agricultural sector in the legal systems of national emissions ceilings in the European Union, and in particular the requirements of the amended legal basis in this respect – Directive No 2016/2284 of 14 December 2016 on the reduction of national emissions of certain atmospheric pollutants, amending Directive 2003/35/EC and repealing Directive 2001/81/EC. This law, in addition to the Nitrates Directive, is currently one of the most important regulations of EU law on protection against environmental pollution from agricultural sources. Among the pollutants covered by the reduction obligation under Directive 2016/2284 NEC, ammonia is the most critical pollutant of agricultural origin, hence the crucial importance for agriculture of the measures aimed at reducing emissions of this substance. These measures are mainly of an optional nature and it is up to the Member States to determine how to achieve the national reduction target. It is therefore necessary to design the right mix of measures and match them with the different types of agricultural activities when developing relevant national strategies. It is also necessary to combine them with other regulations, in particular on industrial emissions and water protection, and to address the issues of nitrogen circle in a systemic manner, not only at farm level but also throughout the entire food chain.